Autologous bone marrow derived stem cells in the treatment of complex anal fistula - Raslan, Mohamed M.; Ayoub, Mahmoud A. (International Surgery Journal, 2018)
Background: Treatment of anal fistula shows a great conflict between preservation of continence and eradication of sepsis. Stem cells extracted from bone marrow are able to home to inflamed tissues and repair injured ones. The aim of this study is to present the early results of injection of stem cells to tracts of complex recurrent fistulae. The primary outcome of the study is the healing of the complex fistula secondary outcomes include safety profile of the procedure. Methods: 15 patients having complex anal fistulae. To prepare stem cells, bone marrow aspiration was performed under complete aseptic conditions. After several steps for isolation, viability testing and preparation, stem cells were suspended in sterile saline for injection in the patients. The internal opening was identified and closed then curettage of the tract with injection of cell suspension simultaneous with fibrin glue followed by injection of stem cell suspension around the tract and external opening finally it was closed. The first evaluation was performed after 8 weeks, a final evaluation after one year. Results: Categorized into three groups (a) complete healing 8 patients (53.3%). (b) Incomplete healing 4 patients (26.7%) (c) Recurrence 3 patients (20%) No incontinence, abnormal tissue growth or major adverse effects were reported. Conclusions: Use of autologous bone marrow-derived stem cells in anal fistula treatment is a recent modality with variable rates of success. Despite the rate of failure or incomplete healing but it still provides a solution to avoid continence impairment. It needs better evaluation with larger sample size, with long-term follow up. literatures.